PENILAIAN PRESTASI KERJA PENDIDIK DAN TENAGA KEPENDIDIKAN BERDASARKAN SASARAN KERJA DAN PERILAKU KERJA - Mufasirul Bayani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Teachers are one of the components that play an important role in achieving the goals in the vision and mission of educational units, which in turn determine the goals of national education. Professors who have good achievements and performance will have a positive impact on student growth and school sustainability, as well as on existing teaching staff. The research method in this article uses the library research method (Library Research) this research method concerns the method of collecting library data, Data collection techniques in this study use documentation and analysis techniques, The data studied uses critical analysis. Critical analysis usually focuses on certain views or values that are believed by researchers related to the problem of improving the quality of education - and documents - documents related to the problems studied by researchers. As a conclusion from the findings of this study, the writing above shows that what is meant by Job Performance Assessment is a system used to evaluate whether an employee as a whole has done his job well. This does not only cover the physical part of his job; it also includes many variables, such as work ability, discipline, team interaction, initiative, and leadership possibilities. This process is part of performance management that begins with formulating employee performance planning, which includes setting employee work targets (SKP) and measuring aspects such as quantity, quality, time, and cost in each task related to their position (pebriansyah, wilodati, & komariah, n.d). Employee work target (SKP) assessment is carried out by comparing actual performance achievements with previously set targets.